2014
DOI: 10.3749/canmin.1400030
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium and Magnetite Intergrowths From the Loma Peguera Chromitite, Dominican Republic, and Relevance to the Debate Over the Existence of Platinum-Group Element Oxides and Hydroxides

Abstract: Two small grains, about 50 × 60 × 70 μm in size, occurring in the chromitite associated with the altered harzburgite of Loma Peguera (Dominican Republic) have been investigated by electron microprobe analyses, X-ray computed tomography, and X-ray diffraction. Electron microprobe data indicate the grains to be composed of Ru, Os, Ir, Fe, and O. The obtained composition is similar to those reported from podiform chromitites worldwide and often reported as evidence for the existence of PGE-bearing oxide minerals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…As can be seen in Figure , Ru–Os–Fe grains from Loma Peguera plot close to results published by Zaccarini et al. (), whereas compositions of Ru–Os–Fe grains from Loma Larga reveal a clear Fe‐enrichment trend towards the field of ruthenian hexaferrum (Mochalov et al, ).…”
Section: Mineralogy Of Fe‐rich Oxygen‐bearing Ru–os Compoundssupporting
confidence: 88%
See 2 more Smart Citations
“…As can be seen in Figure , Ru–Os–Fe grains from Loma Peguera plot close to results published by Zaccarini et al. (), whereas compositions of Ru–Os–Fe grains from Loma Larga reveal a clear Fe‐enrichment trend towards the field of ruthenian hexaferrum (Mochalov et al, ).…”
Section: Mineralogy Of Fe‐rich Oxygen‐bearing Ru–os Compoundssupporting
confidence: 88%
“…The nature of these compounds has, nonetheless, remained uncertain. Recently, Zaccarini et al () analysed two Fe‐rich and oxygen‐containing Ru–Os compounds found in chromitites from Loma Peguera (Dominican Republic) using X‐ray computed tomography and X‐ray diffraction. They concluded that these grains consisted of “a fine intergrown of ruthenium and magnetite not detectable at the scale of the electron microprobe” and that desulphurisation of primary PGM (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its composition suggests that the Sulawesi laurites, even the crystals found in contact with secondary silicates, were not affected by post-magmatic alteration, as observed in laurites associated with other ophiolitic chromitites [12,14,[57][58][59][60][61][62][63][64][65]. During the alteration processes, laurite released S that was replaced by Fe and O to form a fine intergrowth of native ruthenium and magnetite [61] or it has lost part of the Os and Ir to form Ru-rich laurite [14]. Therefore, we can use the analyzed laurite to model the mechanism of its crystallization at high temperature.…”
Section: Origin Of the Pgm In The Sulawesi Chromititesmentioning
confidence: 99%
“…Primary magmatic PGM are laurite, erlichmanite, Os-Ir-Ru alloys, cooperite, Rh-pentlandite, kashinite, and Pt-Fe alloys. It is uncertain whether they are true PGE oxides, or correspond to a mixture of Ru-rich alloys and Fe oxide (magnetite) such as those found in Loma Peguera chromitite described by Zaccarini et al (2014). In particular, the secondary PGM assemblage consists of Ru-Os-Ir-Fe-O compounds, Pt-Pd-Fe-Ni-Cu-Co alloys, and potarite.…”
Section: Sample Provenance and Previous Workmentioning
confidence: 99%